2018
DOI: 10.1016/j.biopha.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of antitumor drugs in combination with propolis on canine osteosarcoma cells (spOS-2) and mesenchymal stem cells

Abstract: The combination of lower concentrations of antitumor drugs (carboplatin - CARB, doxorubicin - DOX, and methotrexate - MET) with propolis was investigated against canine osteosarcoma (spOS-2) and mesenchymal stem cells (MSC) in vitro. The mechanism of action in the combinations was analyzed. spOS-2 cells were incubated up to 72 h with propolis (50 μg/ml) alone or in combination with CARB (10-400 μmol/l), DOX (0.5-2 μmol/l) or MET (50-200 μmol/l). Cell viability was assessed by MTT assay, apoptosis/necrosis by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Propolis made by Africanized honeybees enhanced the cytotoxic effect of carboplatin against canine osteosarcoma cells (Bernardino et al, 2018). In our study, EEP improved DTX cytotoxic effects against MCF-7 cells.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Propolis made by Africanized honeybees enhanced the cytotoxic effect of carboplatin against canine osteosarcoma cells (Bernardino et al, 2018). In our study, EEP improved DTX cytotoxic effects against MCF-7 cells.…”
Section: Discussionsupporting
confidence: 60%
“…Brazilian green propolis exerted a cytotoxic activity against lung cancer A549 cells and laryngeal epidermoid carcinoma HEp-2 cells by inducing apoptosis (Fri on-Herrera, Díaz-García, Ruiz-Fuentes, Rodríguez-Sánchez, & Sforcin, 2015;Silva, Fri on-Herrera, Bartolomeu, Gorgulho, & Sforcin, 2017). This ethanol solution extract of propolis (EEP) also enhanced the action of an antitumor agent (carboplatin) against canine osteosarcoma in vitro (Bernardino, Bersano, Lima Neto, & Sforcin, 2018). In addition, EEP displayed an immunomodulatory action in monocytes and dendritic cells, stimulating the initial steps of the immune response (Búfalo, Bordon-Graciani, Conti, Golim, & Sforcin, 2014;Conti et al, 2016;.…”
mentioning
confidence: 99%
“…[40] There is no information available on the ethnopharmacological activity of Colombian propolis associated with the antitumor effect, except for our own previous reports in which it was shown that EEP induced early and late apoptosis, related to the alteration of mitochondrial membrane potential, likewise, a significant decrease in the invasion, in canine osteosarcoma cells. [41,42] In the first place, the characterization consisted in evaluating proliferation, the exponential phase was established between 72 and 96 hr, a period of time in which the cell confluence was close to 70%, which could suggest that contact stimulates cell growth. These results coincide with tests carried out in the characterization of primary culture fibroblasts cultured with 10% SFB by other authors.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…We found that all propolises have less cytotoxic effect BEAS2B cell line than A549 cell line showed in Tablo 4. It is tested that the combination of lower concentrations of antitumor drugs (carboplatin -CARB, doxorubicin -DOX, and methotrexate -MET) with propolis was investigated against canine osteosarcoma (spOS-2) and mesenchymal stem cells (MSC) in vitro [29]. They found that propolis alone exerted no cytotoxic action against spOS-2 cells, whereas CARB (400, 200 and 100 μmol/l) exhibited the highest cytotoxic effects comparing to DOX and MET.…”
Section: Table 4 Ic50 (Mg/ml) Values Of Propolis Samples On A549 Celmentioning
confidence: 99%